The potentially therapeutic effects of ascorbic acid in different cell line in attempt to reduce the risk of radiation therapy - Rasha S. Shams El Dine; Heba T. Youseef; Ashraf K. Awaad; Sabahh I. Hammoury; Ehab I. Mohamed (Scientific Reports)
Abstract Leukemia is the most common type of serious, life-threatening cancer that requires the immediate initiation of therapy. Ascorbic acid (AsA), commonly known as Vitamin C, has been gaining attention due to its antioxidant activity as a potential treatment for human malignancies. In this study, the THP-1 monocytic cell line was treated with two doses of AsA: a low dose (L-AsA, 2.5 µg/mL) and a high dose (H-AsA, 5 µg/mL), while the K562 lymphocytic cell line was treated with two doses of AsA: a low dose (L-AsA, 4 µg/mL) and a high dose (H-AsA, 8 µg/mL). After a 24-h incubation period, all cells were exposed to different doses of X-radiation (2, 4, 8 Gy). The viability of THP-1 and K562 treated by AsA was assessed using the MTT assay. Additionally, we evaluated apoptosis, autophagy, proliferation, cell cycle progression, hypoxia-inducible factor (HIF-1), malondialdehyde (MDA), and total antioxidant capacity (TAC). Our study demonstrated that AsA, in combination with X-radiation, induced significant apoptosis and notably reduced Ki67 levels in human leukemia THP-1 cells. Furthermore, X-radiation caused DNA damage, leading to cell cycle arrest at the G0/G1 phase in THP-1 cells. Moreover, AsA significantly reduced HIF-1 levels, which are essential for the survival of tumor cells in hypoxic conditions. We also found that the administration of AsA in combination with X-radiation had a synergistic and dose-dependent effect on THP-1 and K562 cells. Notably, the combination of L-AsA with 2 Gy X-radiation showed a more pronounced effect than 8 Gy X-radiation alone. These results suggest that AsA has promising anti-proliferative, pro-apoptotic, and autophagic effects on leukemic cells. Furthermore, the dose of X-radiation may be reduced when combined with AsA in an effort to minimize its potential side effects.